Diagnosis Of Intrauterine Pneumonia in Premature Infants (Texas Journal of Medical Science, 2024)
The gestational age of the subjects was 22–36 weeks. Tensiometric blood parameters in the group of premature newborns with VUP and RDS suggest that they have congenital intrapartum pneumonia. When Ds2 < 4.2 × 103 N/m and k2 > 3.3 × 103 s–1, it can be stated that a premature newborn with respiratory disorders has VUP. We recommend using these indicators in the early and differential diagnosis of intrauterine pneumonia